EXPLORING ESP STUDENTS’ ENGLISH SKILLS BY “ENGLISH TALENT COMPETITION” - Siti Asiyah (JALL (Journal of Applied Linguistics and Literacy), 2018)
Designing ESP course sometimes is not easy as designing general English course. It needs some efforts to handle and realize it because many aspects should be considered in conducting it, such as analyzing students’ needs, formulating goals and objectives, conceptualizing the content, selecting and developing materials, evaluating, getting students’ feedback, etc. Still, those are not enough for serving ESP students in learning English. Many approaches, methods, strategies are also needed in order the ESP students are interested in joining ESP course. As a practitioner of ESP, the writer always tries to find and conduct appropriate and effective programs which can encourage and explore ESP students’ English skills. One of them is English Talent Competition (ETC). It is an annual program conducted by Language Center of Universitas Muhammadiyah Ponorogo since 2014. This study aims at sharing an idea about the implementation of ETC in order to motivate ESP students improve and develop their English skills.Keywords: ESP Students; English Skills; English Talent Competition